2020
DOI: 10.1002/advs.202000283
|View full text |Cite
|
Sign up to set email alerts
|

Autogenous Production and Stabilization of Highly Loaded Sub‐Nanometric Particles within Multishell Hollow Metal–Organic Frameworks and Their Utilization for High Performance in Li–O2 Batteries

Abstract: Despite sub-nanometric particles (SNPs) having unique abilities such as maximized atom-utilization efficiency and governable catalytic selectivity, [1,2] a breakthrough solution that allows not only to originate SNPs and also to preserve single or a few atoms is still required. SNPs are typically stabilized through agglomeration due to their unsaturated surface bonds, [3] even after being synthesized by complex processes, so that the strong interactions with solid supports have been quite successful in stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Chemie stable ZIF-8 shell and water-unstable ZIF-67 core to prepare the hollow structures. [79] They found that unstable ZIF-67 core could be transformed into sub-nano Co(OH) 2 ,l eaving ac avity and aZ IF-8 shell, when exposed to am inority of water. Even multi-shell hollow MOF could be obtained by selective transformation of the unstable MOF.T his work provides an idea to precisely transform the targeted unstable MOF core phase to get the hollow structure.…”
Section: Methodsmentioning
confidence: 99%
“…Chemie stable ZIF-8 shell and water-unstable ZIF-67 core to prepare the hollow structures. [79] They found that unstable ZIF-67 core could be transformed into sub-nano Co(OH) 2 ,l eaving ac avity and aZ IF-8 shell, when exposed to am inority of water. Even multi-shell hollow MOF could be obtained by selective transformation of the unstable MOF.T his work provides an idea to precisely transform the targeted unstable MOF core phase to get the hollow structure.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, dinuclear Co(OH) 2 sub-nanometric particles (SNP) within multishell hollow ZIF-8 (H-ZIF-8[nS], where n is the number of shells) were autogenously synthesized by Kang and co-workers (Fig. 3d) [85]. First, the stable MOF (ZIF-8) layers effectively transferred ethylene glycol (EG) isolated water molecules to the decomposable MOF (ZIF-67) layers through hydrophobic micropores.…”
Section: Mof Compositesmentioning
confidence: 99%
“…stable ZIF-8 shell and water-unstable ZIF-67 core to prepare the hollow structures. [79] They found that unstable ZIF-67 core could be transformed into sub-nano Co(OH) 2 ,l eaving ac avity and aZ IF-8 shell, when exposed to am inority of water. Even multi-shell hollow MOF could be obtained by selective transformation of the unstable MOF.T his work provides an idea to precisely transform the targeted unstable MOF core phase to get the hollow structure.…”
Section: Selective Phase Transformationmentioning
confidence: 99%